Evolutionary Norm Enforcement - Werner Güth; Axel Ockenfels (Center for Economic Studies and ifo Institute (CESifo), 2000)
Applying an indirect evolutionary approach with endogenous preference formation, we show that a legal system can induce players to reward trust even if material incentives dictate to exploit trust. By analyzing the crowding out or crowding in of trustworthiness implied by various verdict rules, we can assess how a court influences the share of kept promises of truly trustworthy players who evolutionarily evolved as trustworthy and of opportunistic players who are only trustworthy if inspired by material incentives.
Keywords: 330